Zinc and boron availability in soils and impact of carriers on crop productivity - Jyolsna V K (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2005)
A study entitled “Zinc and boron availability in soils and impact of carriers on crop productivity” was carried out at College of Agriculture, Vellayani 2003-2005 to monitor the effect of moisture levels with and without FYM on the availability of B and Zn in three types of soil viz., red, laterite and Onattukara sandy and the influence of carriers of Zn and B on tomato. The experiment consisted of two parts viz., incubation study and separate pot culture experiments with B and Zn. The physico-chemical analysis of soils used for incubation study was done using suitable analytical procedures. Incubation study was conducted at the laboratory to monitor the availability of B and Zn in red, laterite and Onattukara sandy soils. Two kg of each type of soil was taken in earthern pots of uniform size and incubated for two months at three moisture levels viz., air dry, field capacity and full saturation with and without FYM. The experiment was laid out in CRD with six treatments. They were, T1 – Air dry, T2 – Field capacity, T3 – Full saturation, T4 – T1 + FYM, T5 – T2 + FYM and T6 – T3 + FYM. Soil samples were drawn at fortnightly intervals and analysed for the available content of boron and zinc following standard analytical procedures. Separate pot culture experiments were conducted to study the influence of B and Zn using laterite soil on growth, yield and quality of tomato. They were laid out in CRD with treatments viz., T1 – fertilizers alone as per POP, T2 – fertilizers and FYM as per POP, T3 - T1 + B/Zn @ 0.5 /2.5 kg ha-1, T4 – T1 + B/Zn @ 1.0/5.0 kg ha-1, T5 – T1 + B/Zn @ 1.5/10 kg ha-1, T6 – T2 + B/Zn @ 0.5/2.5 kg ha-1, T7 – T2 + B/Zn @ 1.0/5.0 kg ha-1 and T8 – T2 + B/Zn @ 1.5/10.0 kg ha-1. Observation on various biometric and yield parameters had been recorded. Soil, plant and fruit analysis were done using standard analytical procedures. From the incubation study, it can be seen that B availability was more at full saturation condition than at air dry and field capacity moisture regimes in all the three soils. It was minimum at air dried state of soil. Available Zn recorded maximum value at air dried state than at field capacity and full saturation moisture regimes. The influence of B and Zn on the growth, yield and quality of tomato can be clearly understood from the pot culture experiments. Plant height and number of primary branches showed significant increase with B and Zn application. Yield, B : C ratio and quality parameters were higher in the treatments which comprise B/Zn along with FYM. Available K in soil after pot culture increased with increase in levels application of boron. The same trend was shown by DTPA-extracted Zn and Cu. Available Fe and Mn decreased by B application. Soil B increased with increase in level of B application. Plant content of these nutrients showed the same trend as that of soil content. Available P, Fe, Mn and Cu decreased with increase in levels of Zn application in the pot culture experiment with Zn. Soil available Zn increased with increase in level of application of Zn. Plant nutrient content showed considerable variations. There was an increasing trend for uptake of nutrients from T1 to T8 as there was an increase in total dry matter production in both the experiments. From the results cited above it can be confirmed that B and Zn fertilization has an important role in improving yield and quality of tomato. The highest yield, quality and B : C ratio were obtained when B was applied @ 1.5 kg ha-1. This indicates that further experiments may be conducted by raising the level of B above 1.5 kg ha-1 to verify its effect on contributing to further increase in yield. In the experiment with Zn, though the yield was the highest in T8, the B : C ratio was higher in T7 than in T8 . This indicates that economic yield was obtained when Zn was at 5 kg ha-1. For the purpose of formulating recommendations on application of B and Zn, more field studies need to be conducted.